Lingkungan, Konteks Politik, dan Budaya dalam Pengembangan Kebijakan Kesehatan: Tinjauan Literatur - Chreisye K. F. Mandagi; Channtika F. Lupi; Nursayla Faradila; Amabel O. Kesek; Meyty A. F. Mangosa; Lovely K. Tulung; Brigitha V. Anyal (KOLONI, 2026)
Health policy development is often viewed as a rational, evidence-based process; however, in practice, it is heavily influenced by environmental, political, and cultural factors. This article aims to critically examine how these three factors both shape and constrain health policy. The method employed is a literature review of publications from the past five years. The results indicate that a technocratic approach to health policy tends to overlook the complexity of local contexts, while political and cultural factors often serve as the primary determinants of a policy’s success or failure. Therefore, a more contextual and integrative policy approach is needed.